(untitled) (Práxis Educativa, 2022)
The coordination between the university faculty is a key aspect for the improvement in the initial training that is offered to future secondary education teachers in Spain. In the research presented, the content studied in the specialty of Social Sciences is analyzed, but mainly the activities that are implemented in the different subjects. A mixed methodology has been followed - qualitative, qualitative-, with an analysis focused on the students’ perception of two universities - university of Alicante and University of Valencia - during the 2020-2021 course, collected through questionnaires with closed and open questions, which allowed the participants’ story. The results obtained show the repetition of content and activities between the different matters of the Master, as well as the predominance of the amount on the quality of the latter, perceiving a significant change towards its realization cooperatively in small group. Keywords: Teaching coordination. Curricular contents. Learning activities.